Multiplex Ligation-Dependent Probe Amplification for Simultaneous Identification of Bungarus multicinctus and Its Common Adulterants in a Single Assay - Zhou, Yuxin; Nie, Jing; Yu, Shiqi; Hu, Zhigang; Wang, Bo (Frontiers in Pharmacology, 2020)
Abstract: Bungarus multicinctus, an important traditional Chinese medicine, possesses remarkable medicinal activities, while lots of adulterants from other species were misused as B. multicinctus for its large demand and resource starvation. In order to accurately identify B. multicinctus and its common adulterants such as Sinonatrix annularis, Xenochrophis flavipunctatus, Deinagkistrodon acutus and Naja atra, a simultaneous identification method was designed with multiplex ligation-dependent probe amplification (MLPA) analysis. Five species-specific MLPA probe-couples for B. multicinctus and its common adulterants were designed based on the universal primer amplified COI sequences, which can specifically detect the five species with no mutual interference, and sensitivity analysis showed as less as 5% B. multicinctus or 8.75% adulterants in the mixed samples can be identified in a MLPA assay, especially, the relative quantity of the adulterants can be also inferred based on the MLPA peak area values. Moreover, the results of the present study confirmed the effectiveness of this technique in terms of simultaneous identification of B. multicinctus and its common adulterants in an assay, which has great potential for ensuring the safety of this commercially valuable snake species.